Numerical simulation on the load-bearing capacity of CFRP-strengthened concrete arches - Xinyu Song; Zhengyuan Yue; Erhu Zheng; Jiannan Zhou; Ying Xu; Xinli Kong; Bo Wang; Yinzhi Zhou (Case Studies in Construction Materials, 2024)
To investigate the bearing capacity of concrete structures strengthened by carbon fiber reinforced composite (CFRP), this study conducted numerical simulation research on seven CFRP-strengthened concrete arch structures with five different strengthening schemes. The finite element model was established by HYPERMESH, the simulation results were compared with the experimental results to verify the accuracy of the model. Based on this, the interfacial bonding performance of concrete and CFRP under different strengthening schemes was analyzed, and the static damage mode of the reinforced concrete arch structure was revealed. The results indicate that the application of CFRP to the surface of a concrete arch will increase the linear segmental stiffness, cracking load, and ultimate load of the structure. The five strengthening schemes in this paper provide enhancements ranging from 2.9 % to 57.6 % for concrete arch cracking loads, from 3.3 % to 14.7 % for ultimate loads, and from 1.1 % to 17.6 % for stiffness. If both the inner and outer sides are strengthened with CFRP, the ultimate bearing capacity of the arch structure can be significantly enhanced. Circumferential wrapping of CFRP can delay the concrete cracking and further enhance the bearing capacity of the arch, and the strengthening effect can be maximized. This study can provide a valuable reference for the strengthening of old concrete arch structures and the construction of newly assembled arch tunnels.